Smart HPP: Design of a Web-Based COGS Calculator for the Manufacturing Industry for MSMEs - Indrawan, Andi Kusuma; Arisudhana, Aditya; Akbar, Dharmawan Iqbal; Sukya, Fadelis; Amerieska , Siti; Binti Abu Bakar, Siti Anis Nadia (Jati: Jurnal Akuntansi Terapan Indonesia, 2026)
This study aims to develop a COGS (Cost of Goods Sold) calculation website for MSMEs in the manufacturing sector (Smart-HPP) to enable them to make more accurate business decisions. The COGS calculation model on this (Smart-HPP) uses full costing and variable costing. This research was conducted because MSMEs still have difficulty calculating the appropriate COGS. The website was created to facilitate user access. This (Smart-HPP) will later be accessible to Indonesian manufacturing MSMEs. This study uses the results of 2 MSME interviews to understand the problems and needs of MSMEs. Two manufacturing sector MSMEs are the subjects of this research. This study employs a research and development (R&D) approach based on the ADDIE model. The results of this study indicate that the application can run according to the needs of MSMEs. This (Smart-HPP) can be used to determine COGS and make simple decisions because it contains information on product cost allocation.